Tinjauan Parameter Temperatur, Kecepatan Angin dan Nitrogen Dioksida (No2) di Terminal Mardika Kota Ambon - Kornelis U. Rumselly; Zulfikar Peluw; Amry Jusuf (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background. City Ambon is Mother city province Maluku Which consists of from 5 sub-district, and has a population that is increasing day by day Which not balanced with the area. The density of motorized vehicles is increasing also increased with the presence of various vehicles. This will potentially increase the level of pollution air Which caused by by a number of pollutant Which produced from disposal smoke motorized. Objective. For know quality air ambient at Mardika terminal Ambon city. Methods. Type study This is study descriptive that is study about inspection level nitrogen dioxide (NO 2 ) at the terminal Mardika city Ambon, with study direct to field For to obtain sample Which Then done examination at the Environmental Health Technology Center (BTKL) Laboratory, Ambon. Results. Measurement temperature at the terminal Mardika Ambon Sunday First 39.9 ºC, Sunday second -34.4 ºC, Sunday third 34.2 ºC, Sunday fourth 29.4 ºC. Measurement speed wind in terminal Mardika Ambon on Sunday First 0.3-1.7 m/sec, Sunday second 1.8 m/s, Sunday third 0.3-1.7 m/sec, Sunday fourth 1.2-3.9 m/sec. Measurement level NO 2 in terminal Mardika Ambon that is Sunday First <5.22 µg/Mm³, Sunday second <5.22 µg/Nm³, Sunday third <5.22 µg/Nm³, Sunday fourth <5.22 µg/Nm³. Conclusion. Measurement Temperature, Speed Wind and Nitrogen Dioxide (NO 2 ) all results measurement fulfil standard.